2020
DOI: 10.1038/s41598-020-71684-6
|View full text |Cite
|
Sign up to set email alerts
|

Parallel assessment of albuminuria and plasma sTNFR1 in people with type 2 diabetes and advanced chronic kidney disease provides accurate prognostication of the risks of renal decline and death

Abstract: Identification of people with diabetes and chronic kidney disease at high-risk of early mortality is a priority to guide intensification of therapy. We aimed to investigate the complementary prognostic value of baseline urine albumin-to-creatinine ratio (uACR) and plasma soluble tumour necrosis factor receptor-1 (sTNFR1) with respect to early mortality and renal functional decline in a population with type 2 diabetes and advanced chronic kidney disease. We measured plasma sTNFR1 in people with type 2 diabetes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
(42 reference statements)
1
4
0
Order By: Relevance
“…Predictive performance of the biomarkers was further enhanced when incorporated alongside clinical variables. sTNFR1 and NGAL were the two most important biomarkers to classification by random forests, reaffirming their predictive value, which has been demonstrated across multiple cohorts (23 25,27,38 40). C-reactive protein ranked as the fifth most important variable to random forest classification of the composite renal and mortality end point, both in models trained on serum biomarkers alone and in models trained on both clinical variables and biomarkers, which further endorses its role in prognosticating the risk of renal functional decline in CKD (41,42).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Predictive performance of the biomarkers was further enhanced when incorporated alongside clinical variables. sTNFR1 and NGAL were the two most important biomarkers to classification by random forests, reaffirming their predictive value, which has been demonstrated across multiple cohorts (23 25,27,38 40). C-reactive protein ranked as the fifth most important variable to random forest classification of the composite renal and mortality end point, both in models trained on serum biomarkers alone and in models trained on both clinical variables and biomarkers, which further endorses its role in prognosticating the risk of renal functional decline in CKD (41,42).…”
Section: Discussionsupporting
confidence: 61%
“…However, the latter cohort of patients exclusively had type 2 diabetes for a median duration of 10 years and were enrolled up to a decade before patients in this study (10). The eGFR slope trajectory of this cohort was more similar to, albeit still lower than, a group of patients with type 2 diabetes and CKD (mean eGFR of 42 ml/min per BSA) enrolled in Dublin, Ireland during 2014-2015, in whom annual change in eGFR was 22 ml/ min per BSA per year (27). Thus, improvements in CKD management and a lower prevalence of diabetes (25%) in this study cohort may explain the modest rates of renal functional decline observed.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Albuminuria represents a marker of microvascular disease preceding the loss of kidney function, accumulation of cSVD lesions and stroke [ 36 , 63 , 64 , 65 ]. After BBB breakdown occurs, several mechanisms may explain the connection between UACR and cognitive impairment, including an exacerbated inflammatory response.…”
Section: Resultsmentioning
confidence: 99%
“…The previous reports showed inconsistent conclusions about the predictability of sTNFR1 levels for cardiovascular and renal outcomes in subjects with stable coronary artery disease or advanced CKD versus subjects without apparent signs of cardiovascular or renal complications. 14 , 25 28 The discrepancies might be originating from the differences of characteristics of participants or definitions of outcomes. Our cohort enrolled the subjects with and without cardiovascular or renal complications at baseline.…”
Section: Discussionmentioning
confidence: 99%